Identification of QTLs for Domestication-Related Traits in Zombi Pea [Vigna vexillata (L.) A. Rich], a Lost Crop of Africa - Amkul, Kitiya; Somta, Prakit; Laosatit, Kularb; Wang, Lixia (Frontiers in Genetics, 2020)
Zombi pea [Vigna vexillata (L.) A. Rich] is a legume crop found in Africa. Wild zombi pea is widely distributed throughout the tropical and subtropical regions, whereas domesticated zombi pea is rarely cultivated. Plant domestication is an evolutionary process in which the phenotypes of wild species, including seed dormancy, pod shattering, organ size, and architectural and phenological characteristics, undergo changes. The molecular mechanism underlying the domestication of zombi pea is relatively unknown. In this study, the genetic basis of the following 13 domestication-related traits was investigated in an F2 population comprising 198 individuals derived from a cross between cultivated (var. macrosperma) and wild (var. vexillata) zombi pea accessions: seed dormancy, pod shattering, days-to-flowering, days-to-maturity, stem thickness, stem length, number of branches, leaf area, pod length, 100-seed weight, seed width, seed length, and seeds per pod. A genetic map containing 6,529 single nucleotide polymorphisms constructed for the F2 population was used to identify quantitative trait loci (QTLs) for these traits. A total of 62 QTLs were identified for the 13 traits, with 1–11 QTLs per trait. The major QTLs for days-to-flowering, stem length, number of branches, pod length, 100-seed weight, seed length, and seeds per pod were clustered in linkage group 5. In contrast, the major QTLs for seed dormancy and pod shattering belonged to linkage groups 3 and 11, respectively. A comparative genomic analysis with the cowpea [Vigna unguiculata (L.) Walp.] genome used as the reference sequence (i.e., the genome of the legume species most closely related to zombi pea) enabled the identification of candidate genes for the major QTLs. Thus, we revealed the genomic regions associated with domestication-related traits and the candidate genes controlling these traits in zombi pea. The data presented herein may be useful for breeding new varieties of zombi pea and other Vigna species.